Normal immunoglobulin G (IgG) for therapeutic use (intravenous Ig) contain antiidiotypic specificities against an immunodominant, disease-associated, cross-reactive idiotype of human anti-thyroglobulin autoantibodies. - Dietrich, G (1990)
Pooled normal polyspecific IgG for therapeutic use (IVIg) contain anti-idiotypes against idiotypic determinants expressed by autoantibodies from patients with a variety of autoimmune diseases. In the present study, antiidiotypes in IVIg are shown to recognize a cross-reactive idiotype on human anti-thyroglobulin (TG) autoantibodies, that was defined by heterologous antiidiotypic antibodies, termed anti-T44 antibodies. The T44 idiotype is located outside the antibody-combining site of anti-TG autoantibodies. F(ab')2 fragments from anti-T44 antibodies inhibited the binding of IVIg to affinity-purified F(ab')2 anti-TG autoantibodies. Anti-T44 antibodies bound to F(ab')2 fragments of patients' antibodies, which were retained on an affinity column of Sepharose-bound F(ab')2 fragments from IVIg, but not to F(ab')2 fragments from the effluent of the column. The T44 idiotype was expressed on antibodies that bound to IVIg from eight of nine patients with autoimmune thyroiditis, but not on IVIg-binding Igs from healthy individuals. A small amount of the T44 idiotype was also expressed on the fraction of IVIg that bound to itself upon affinity chromatography. The T44 idiotype was cross-reactive between antibodies from patients with autoimmune thyroiditis. Thus, IVIg contain antiidiotypic antibodies directed against an immunodominant disease-associated cross-reactive alpha-idiotype of human anti-TG autoantibodies. These results support the concept that IVIg may be beneficial in selected autoimmune diseases by modulating the function of the idiotypic network.